Cementless Fixation of Osteoporotic VCFs Using Titanium Mesh Implants (OsseoFix): Preliminary Results. (2nd June 2014) - Eschler, Anica; Ender, Stephan Albrecht; Ulmar, Benjamin; Herlyn, Philipp; Mittlmeier, Thomas; Gradl, Georg
Abstract : Introduction . Vertebral compression fractures (VCFs) affect 20% of people over the age of 70 with increasing incidence. Kypho-/vertebroplasty as standard operative procedures are associated with limitations like cement leakage, limited reduction capabilities, and risk for adjacent fractures. To address these shortcomings, we introduce a new minimal invasive cementless VCF fixation technique. Methods . Four patients (72.3 years, range 70–76) with VCFs type AO/Müller A1.3 and concomitant osteoporosis were treated by minimal invasive transpedicular placement of two intervertebral mesh cages for fracture reduction and maintenance. Follow-up included functional/radiological assessment and clinical scores and averaged 27.7 months (24–28). Results . Endplate reduction was achieved in all cases (mean surgery time: 28.5 minutes). Kyphotic (KA) and Cobb angle revealed considerable improvements postoperatively (KA 14.5° to 10.7°/Cobb 10.1° to 8.3°). Slight loss of vertebral reduction (KA: 12.6°) and segment rekyphosis (Cobb: 10.7°) were observed for final follow-up. Pain improved from 8.8 to 2.8 (visual analogue scale). All cases showed signs of bony healing. No perioperative complications and no adjacent fractures occurred. Conclusion . Preliminary results in a small, selected patient collective indicate the ability of bony healing for osteoporotic VCFs. Cementless fixation using intravertebral titanium mesh cages revealed substantial pain relief, adequate reduction, and reduction maintenance without complications. Trial registration number is DRKS00005657, German Clinical Trials Register (DKRS).